Identification of Novel Gene variants in Patients with Alzheimer's Disease by Whole Exome Sequencing - Xiaodong Pan; Murong Yang; Jingjing Xiang; Qi Pan; Menghao Yang; Jing Xia; Lang Cui; Ruijie Luo; Qinlin Lou; Chen Zhou; Yiran He; Kuichun Zhu (Annals of Alzheimer's and Dementia Care - Peertechz Publications, 2020)
Alzheimer's Disease (AD) affects millions of elderly people, many of the patients partially or completely lost the capability to maintain independent daily living [1-3]. Limited progress was made in the past decades in the designing intervention approaches that could effectively delay the progression of the disease. Novel leads are in urgent need. Next Generation DNA sequencing (NGS) technology has been widely used in the basic biomedical research and molecular diagnosis in clinical settings. Few NGS studies in AD were reported, and those reported focused on rare variants from a few genes, such as APP, PSEN1, PSEN2, SORL1, and TREM2 [4-6]. Recently results from some Whole Exome Sequencing (WES) studies with specimens from AD patients were reported, but a general variant landscape is still missing [7-9]. Accumulated variants of these genes only account for the genetics of a small fraction of AD patients. Genome-Wide Association Studies (GWAS) identified several dozen AD associated genes, but most of the associations are weak [10-12]. We performed a WES study with specimens from AD patients, and we identified several dozen novel gene variants. These novel variants could potentially be causative mutations for AD or variants in association with AD.